The contribution of Luphurise Mawere’s “Things to do so you are able to succeed financially” to African prosperity theology - Davis, Tamie (Missiology, 2023)
Recent scholarship on prosperity theology in Africa has recognized that there has been a tendency to homogenize and flatten its richness and diversity and that more work is needed to understand the nuances of prosperity theology in its local manifestations. This article explores a podcast series produced by Tanzanian Luphurise Mawere from her home at the start of the COVID-19 pandemic. First, it outlines the theology of the podcast and highlights the creation mandate as the dominant feature of it. Second, it locates Mawere’s theology in the mosaic of prosperity theologies in Africa, arguing that her theology ought to be viewed as a legitimate part of prosperity theology in Africa, despite significant differences with other prosperity theologies. Finally, it considers the contribution of Mawere’s theology to African prosperity theology and the study of it, and suggests how it might be applied by mission practitioners.
paid